Effect of density and arrangement of plants of sunflower II. Agronomic characteristics and interception of solar radiation - Schmidt, Eduardo; Silva, Paulo Regis Ferreira da (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of evaluating the effect of sunflower (Helianthus annuus L.) plant density and arrangement of the population on agronomic characteristics and on interception of solar radiation by plants of the cultivar ’Contisol 711’, a research was conducted at Guaíba, RS, Brazil, during the 1983 growing season. Populations of 25.000 and 50.000 plants/ha were tested in five arrangements: two single row spacings, 100 cm and 70 cm apart; two double row systems spaced 150 cm and 200 cm apart (50 cm between rows in the double rows); and one system with plants uniformly spaced within and between rows. The leaf area and harvest index, as well as plant height were higher with, 50.000 than 25.000 plants/ha. On the other hand, plants in the lowest population presented higher biological yield and leaf area per plant and achene moisture at harvest. The single row arrangements presented higher leaf area and biological yield per plant, as well as leaf area index and interception of solar radiation. Double rows showed higher plant height.